Influence of wheel axle stiffness character to the wheel/rail dynamic contact on the straight track - Ma, Weihua; Xu, Zhiqiang; Luo, Shihui; Song, Rongrong (Transport, 2015)
The influence of the wheel axle bending stiffness to the wheel/rail contact dynamic force and wheelset vertical vibration of the linear metro vehicle on a straight track was investigated. Based on a vehicle dynamic model and two kinds of elastic wheelset models, a comparison was carried out between the wheelset vertical vibration and the wheel/rail vertical force. Simulation results showed that the wheelset vibration and the wheel/rail vertical force of the elastic wheelset model were different with that of the rigid wheelset model; this was due to the BM3000 type wheelset not having high enough bending stiffness. In contrast, the result of the elastic wheelset model of the wheelset of the Beijing metro railway vehicle was quite similar to the results of the rigid model since a larger bending stiffness was used. Consequently, the wheelset vibration and wheel/rail vertical force can be decreased by increasing the wheel axle bending stiffness which will improve wheel/rail dynamic contact conditions. First published online: 16 Oct 2013